Algorithm of choice of optimal control of movement of aviation simulator for reproduction of acceleration of sensation - Азарсков, В. Н. (Proceedings of National Aviation University (archive), 1998)
Considered is the problem of synthesis of optimal system of reproduction of pilot acceleration sensation which is reduced to the known problem of synthesis of optimal stabilization system of complicated dynamic object. Given is the algorithm of solution of this problem